Human capital transmission and the earnings of second-generation immigrants in Sweden - Mats Hammarstedt; Mårten Palme (IZA Journal of Migration, 2012)
We compare the earnings and the intergenerational earnings mobility of immigrants with natives in Sweden. We find an overall convergence in average earnings between immigrants and natives across generations. This convergence hides a divergence in average earnings between groups of immigrants with different ethnic origins. We also find that, on average, immigrants have lower intergenerational earnings mobility within groups with similar ethnic backgrounds. Immigrant groups with relatively low intergenerational earnings mobility increased their average relative earnings in the second generation. The interpretation of this is that immigrant groups with a high degree of intergenerational transmission of human capital from parent to offspring improve their position on the labor market across generations.
Keywords: J15; J24; J61; J62; 330; intergenerational income mobility; intergenerational earnings correlation; Becker-Tomes model; ethnic capital; Migranten; Soziale Mobilität; Humankapital; Generationengerechtigkeit; Ethnische Gruppe; Schweden